Intercultural Orientation and Support When Living as a Hispanic-American Expatriate in Jakarta - Cordovez, Ana Cristina Valdez (UI Scholars Hub, 2018)
The population of Hispanic-Americans living in Asia is growing, but there is still a lack of knowledge about their nationalities or cultural background. Past studies and academic research are often too broad as they consider all expatriates as virtually the same. This article will fill this gap by focusing specifically on people originating from Central and South American countries and examining the challenges and adjustment difficulties they face during their assignments overseas. The research was conducted by using a qualitative methodology, hence, in-depth interviews as well as informal conversational interviews were jointly used as methods of data collection, along with theories such as U-curve theory and push-pull theory. The findings indicate that companies need to have a design strategy and full involvement both prior and during the expatriation process, as well as upon repatriation. In addition, it was found that better mechanisms in relation to cross cultural training, good orientation and improved organizational communication for expatriates and their families will enhance their adaptability to and familiarization with the host country environment, which will, in turn, ensure a successful overseas assignment.